Primary immune complex membranoproliferative glomerulonephritis and C3 glomerulonephritis: experience of two rare diseases from a single centre - Barai, Tonmay; Bhatttacharjee, Koushik; Basu, Keya; Dasgupta, Sanjay (International Journal of Research in Medical Sciences, 2025)
Background: This study has been conducted to evaluate and compare the clinicopathological profile and treatment outcome of primary immune complex membranoproliferative glomerulonephritis (IC-MPGN) and C3 glomerulonephritis (C3 GN), two rare glomerular diseases and to find any predictive factors for renal and patient outcome. Methods: A retrospective observational cross-sectional study, conducted at a tertiary care hospital. Patients with biopsy-proven MPGN were included after satisfying the inclusion and exclusion criteria. Detailed history, clinical examinations, laboratory investigations and kidney biopsy were noted. Outcome was recorded at months 3, 6, 12 and at the last available follow-up. Results: Of the 24 subjects enrolled, 11 (45.8%) had primary IC-MPGN and 13 (54.2%) had C3 GN. Nephrotic syndrome is the prevalent presentation. No statistically significant difference was found in respect to clinical and biochemical parameters between two groups. Complement mediated group had more crescent and features of chronicity in renal biopsy. Renal and patient outcome was significantly better in immune mediated group compared to complement mediated group (log rank p=0.015); including complete remission (p=0.003), proteinuria reduction at 3 months (p=0.009), at the last known follow-up (p=0.005). During follow up, hematuria, higher serum creatinine and low median serum albumin were significantly more common in complement mediated group. No significant predictors were found for renal outcome and outcome was not influenced by treatment modality. Conclusions: IC-MPGN and C3 GN are rare glomerular diseases. Although phenotypically similar, C3 GN showed poor outcome. Further multicentric study may help to better understand these diseases to find cost effective treatment.